Transparansi Pengelolaan Anggaran Dana Desa (Studi Kasus di Kecamatan Posigadan, Kabupaten Bolaang Mongondow Selatan) - Atuna, Putri; Hamim, Udin; Abdussamad, Juriko (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze transparency in managing the village fund in Pasigadan Sub-district, South Bolaang Mongondow Regency. Transparency in managing village funds is crucial to ensure that allocation and utilization align with the principles of accountability, participation, and budget discipline. The study employed a qualitative approach with a descriptive research method. Data were collected through interview. Observation, and documentation from several villages in Posigadan Sub-district. The findings show that transparency in managing village fund in the sub-district remains suboptimal. The main challenges identified include limited public access to village financial information, minimal community involvement in planning deliberations and a lack of openness in the management and documentation processes. Although village governments have made efforts to improve transparency, more effective strategies are still needed, such as using information technology and enhancing the capacity of village officials. This study strengthens village governance by emphasizing the importance of transparency to support better village development. The implications of this study highlight the need for stricter policies to enforce principles of transparency and increase community participation in monitoring the village fund.